A simple graphical way of evaluating coverage and directional non-coverages - Freitas, Adelaide (2017)
Evaluation of the coverage probability and, more recently, of the intervalar location of con dence intervals, is a useful procedure if exact and asymptotic methods for constructing con dence intervals are used for some populacional parameter. In this paper, a simple graphical procedure is presented to execute this kind of evaluation in con dence methods for linear combinations of k independent binomial proportions. Our proposal is based on the representation of the mesial and distal non-coverage probabilities on a plane. We carry out a simulation study to show how this graphical representation can be interpreted and used as a basis for the evaluation of intervalar location of con dence interval methods.